Upaya Meningkatkan Motivasi Belajar IPA Peserta Didik Melalui Penerapan Model Quantum Learning di SMP Negeri 7 Makassar - Dedi Riswandi; Nasmur MT Kohar (JURNAL PEMIKIRAN DAN PENGEMBANGAN PEMBELAJARAN, 2024)
This research aims to increase students' learning motivation through the application of the Quantum Learning model. This research is Classroom Action Research. The research was carried out at SMP Negeri 7 Makassar. The research subjects were class VII students. 9 academic year 2023/2024. The object of the research is students' science learning motivation. Data collection techniques use learning motivation questionnaires and learning outcome test instruments. Questionnaire data were analyzed using descriptive statistical analysis. As supporting data, test instruments are used to measure student learning outcomes and improvements. The magnitude of the increase in learning outcomes is based on the N-gain score from the average pretest and posttest. This research was carried out in 2 cycles. Each cycle consists of 2 meetings. Students' learning motivation was measured 3 times, namely pre-cycle, cycle 1, and cycle 2. The research results showed a tendency for students' learning motivation to be in the high category both before and after the cycle. However, there were differences in quantity in each phase of the cycle, this shows the effect of action, especially in cycle 2 where there was an increase in the number of students in the very high learning motivation category and a decrease in the number of students in the moderate learning motivation category. Based on the results of this research, it can be concluded that the application of the Quantum Learning learning model can increase students' learning motivation.